2003
DOI: 10.1111/j.1469-8749.2003.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficient coordination of associated postural adjustments during a lifting task in children with neurodevelopmental disorders

Abstract: Precision grip and concomitant anticipatory postural adjustments were investigated in 11 children (three females, eight males; mean age 9 years 1 month, SD 11 months) with attention‐deficit‐hyperactivity disorder (ADHD); 12 children (three females, nine males; mean age 9 years, SD 7 months) with developmental coordination disorder (DCD), and 13 children (two females, 11 males; mean age 9 years 9 months, SD 11 months) with a combination of ADHD and DCD (ADHD+). There were two comparison groups: an age‐matched g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Other findings suggest motor (walking, standing, catching, dribbling, and kicking) that the balance deficits may reflect cerebellar dysfunctions 38,39 and brain abnormalities at higher levels of cognitive, motor, and vestibular integration 40 . In our study, the significant difference between the ADHD and control groups for standing on each leg is supported by literature [41][42][43] . However, one study by Schlee et al 10 found no difference in performance when balancing on one leg.…”
Section: Discussionsupporting
confidence: 86%
“…Other findings suggest motor (walking, standing, catching, dribbling, and kicking) that the balance deficits may reflect cerebellar dysfunctions 38,39 and brain abnormalities at higher levels of cognitive, motor, and vestibular integration 40 . In our study, the significant difference between the ADHD and control groups for standing on each leg is supported by literature [41][42][43] . However, one study by Schlee et al 10 found no difference in performance when balancing on one leg.…”
Section: Discussionsupporting
confidence: 86%
“…The output of this forward model can then be used in the online control of movement by anticipating the errors (Geuze & Wilson, 2008, Chap. 11;Johnston, Burns, Brauer, & Richardson, 2002;Jucaite, Fernell, Forssberg, & Hadders-Algra, 2003). In our study it seems that children with DCD need more corrections, which due to the timing problems may be too late or too large, resulting in more corrections depicted in erratic reversals.…”
Section: Difference In Force Plate Variables Between Groups At Baselinementioning
confidence: 59%
“…This phenomenon corresponds with the cerebellar hypothesis. The cerebellar hypothesis states that motor difficulties in DCD are due to dysfunction of the cerebellum, resulting in delayed response times, poor coincidence timing, poor anticipation of forthcoming disturbances, dysmetria, mirror movements and large within-child variability over learning trials (Jucaite et al, 2003;Kandel, Schwarz & Jessell, 2000;Visser, 2003). For the predictive, feedforward part of the movement the cerebellar adaptive mechanism is important.…”
Section: Difference In Force Plate Variables Between Groups At Baselinementioning
confidence: 99%
“…In addition, difficulties in neuromuscular coordination might be related to deficits in force control. There is evidence that children with DCD show some deficits in the production of force and explosive power 27 as well as in force control 28 . Of interest to this study is the fact that an equivalent BMI for children of both groups did not reveal the deficiencies of the p DCD group, giving support to the view that the performance of physical fitness tests in the p DCD group might also be determined by the neuromuscular coordination demands of the tasks.…”
Section: Discussionmentioning
confidence: 99%